Meningkatkan Kecerdasan Logika Matematika Anak Usia 5-6 Tahun Melalui Media Game Edukasi di TK Aisyiyah Bustanul Afthal VII Pekanbaru - Nuning Dwi Puspaningrum; Minah Minah; Ihda Hafnita (Jurnal Pendidikan Tuntas, 2023)
The purpose of this study was to improve the mathematical logic intelligence of children aged 5-6 years through educational game media at Aisyiyah Bustanul Afthal VII Kindergarten Pekanbaru. The method used in this research is class action research (Classroom Action Research) with the number of research subjects as many as 20 children consisting of 10 boys and 10 girls. Data collection techniques in this study were observation and documentation. The data analysis technique used in this research is the percentage technique. The results showed that the application of educational game media implemented in Aisyiyah Pekanbaru Kindergarten was carried out in two cycles where each cycle consisted of 3 meetings. The implementation and application of educational game media that researchers do with the help of an observer, namely one of the teachers at Aisyiyah VII Kindergarten Pekanbaru. Shows the results in accordance with what is expected where this educational game media has a positive impact on children's mathematical logic intelligence. in cycle I obtained an average score of 34.9 (43.6%) with the criteria starting to develop. There was an increase in the increase in mathematical logic intelligence in children at Aisyiyah Bustanul Afthal VII Kindergarten Pekanbaru in cycle II with an average score of 65.1 (81.3%) with very good developing criteria (BSB). From the research data above, it can be said that the increase in mathematical logic intelligence in each child has increased from before the research action compared to after the research action with educational game media at Aisyiyah Bustanul Afthal VII Kindergarten Pekanbaru. Keywords: math logic intelligence, educational games, classroom Action Research